Pedestrian Safety and Sustainable Urban Planning: A Literature Review on Walkable City Design - Mehmet Tevfik Seferoğlu; Jafar Allahverdiyev (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Approaching green infrastructure and walking-based urbanism is the need for an hour in an urban context; hence, the life of a cyclic plan becomes essential. This study conducted a literature review addressing measures to improve pedestrian safety and comfort in urban spaces. At the design level, core strategies such as sidewalk expansion, restricted access pedestrian only areas, and integrated green spaces were explored in terms of their contribution to minimizing traffic incidents and promoting sustainable movements. The examination of pedestrian/cycle-centric planning lacks existing research, particularly in determining socioeconomic effects. Through a synthesis of recent studies, this review seeks to provide actionable insights for urban planners and policymakers to promote walkable, safe, and inclusive cities. The findings enhance the understanding of how pedestrian-focused designs improve safety, promote environmental sustainability, and improve public health while providing implications for future research.